Relationship between Urinary Arsenic Level and Urinary Iodine, Radioiodine Uptake, TSH, FT4 Levels: Research is Based on Experimental and Control Groups - Hossain, Md Sharif; Begum, Fatema (Dhaka University Journal of Pharmaceutical Sciences, 2012)
In Bangladesh drinking water is heavily contaminated with arsenic. An estimated 50 million people are at risk from drinking of arsenic contaminated water in Bangladesh and West Bengal in India. Millions of people in many districts of Bangladesh are drinking ground water with arsenic concentrations above acceptable levels (0.05 mg/l) and many of them have already been diagnosed with poisoning symptoms. That is why, in this research an attempt has been made to find the relation between arsenic levels and urinary iodine, radioiodine uptake, thyroid stimulating hormone (TSH) and free thyroxin (FT4) levels in Bangladeshi population. Another purpose has also been made to find the impacts of arsenic level on simple diffuse goiters. This is a case-control analytic study. The study was carried out at the Institute of Nuclear Medicine and Ultrasound, in collaboration with the thyroid out patient department of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. From our analytical results it has been found that, only the variable radioiodine uptake at 24 hours play significant role for reducing the arsenic level. Also, it has been found that iodine deficiency is not only the factor of causing simple diffuse goiter, but arsenic level is also one of the most important factors of causing simple diffuse goiter in Bangladeshi population. DOI: http://dx.doi.org/10.3329/dujps.v10i1.10010 DUJPS 2011; 10(1): 13-20